NEW INSIGHT INTO THE MECHANISM OF ACTION OF ε-ELEMENT ENHANCER IN E. COLI - Nizkorodova , A.S.; Iskakov , B.K. (Eurasian Journal of Applied Biotechnology, 2019)
Epsilon element (ε-element) is a complex translational enhancer capable of promoting the prokaryotic translation efficiency in combination with the Shine-Dalgarno (SD) sequence. However, the detailed mechanism of action of ε-element is unknown, and there is no single hypothesis to explain the available evidence. We here propose a new hypothesis for the mechanism of action of ε-element from the 5′-untranslated region (UTR) of the 10 gene of phage T7 during translation initiation in Escherichia coli. The mechanism of action was considered to be driven by the complementary interaction of ε-element (and its variation εII) with the 3′-end of E. coli 16S rRNA, specifically with the 45th hairpin region. This hypothesis was then applied to currently available data of the influence of ε-element on protein expression in bacterial cells. Several 5′-UTR sequences were constructed containing variations of ε-element, and their properties were predicted according to this new hypothesis and confirmed by measuring the protein expression level. We further applied temperature stresses (cold and heat shock) to these variants to examine their influence on protein expression controlled by various enhancers. Overall, the εII_SD and ε_SD enhancers could significantly increase the protein expression level in E. coli cells under cold shock, representing a 6–9-times increase relative to that obtained with the classical SD sequence.